Meningkatkan Kinerja Pegawai Dinas Perhubungan Kota Parepare: Peran Penting Motivasi dan Disiplin Kerja - Pratama, Ego; Hartati, Hartati; Natsir, Ulfa; Anggerwati, A. Indah (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2023)
The study aimed to assess the impact of work motivation and discipline on employee performance at the Parepare City Transportation Office. Data were collected from 41 employees using observation, interviews, questionnaires, and documentation. The results showed that both work motivation (t=4.330, p<0.05) and discipline (t=2.462, p<0.05) significantly influenced employee performance. Together, these factors accounted for 76.4% of the variance in performance, with the remaining 23.6% potentially influenced by other factors not examined in the study.